Watercolor : the creative experience - Nechis, Barbara (Westport, Connecticut : North Light Publishers, 1978)
Watercolor is a medium which presents infinite possibilities. I choose to explore these possibilities, wherever they may lead, by refusing to restrict myself to methodical rules. I deliberately avoid the approach of paining specific things. There are numerous books available for those who wish to follow this approach.
Introduction -- 1. Materials -- 2. Beginnings -- 3. Development and design -- 4. Glazing -- 5. Developing personal style -- 6. Color portfolio I -- 7. Color portfolio II -- 8. Completions and fixing failures -- 9. Subjects: Landscape ; Snow ; Flowers ; Sailboats ; Buildings ; Trees -- 10. Presentation -- Index.
Includes bibliographical references and index.
Keywords: WATERCOLOR PAINTING -- TECHNIQUES